2018
DOI: 10.4162/nrp.2018.12.3.258
|View full text |Cite
|
Sign up to set email alerts
|

An association between diet quality index for Koreans (DQI-K) and total mortality in Health Examinees Gem (HEXA-G) study

Abstract: BACKGROUND/OBJECTIVESDiet quality scores or indices, based on dietary guidelines, are used to summarize dietary intake into a single numeric variable. The aim of this study was to examine the association between the modified diet quality index for Koreans (DQI-K) and mortality among Health Examinees-Gem (HEXA-G) study participants.SUBJECTS/METHODSThe DQI-K was modified from the original diet quality index. A total of 134,547 participants (45,207 men and 89,340 women) from the HEXA-G study (2004 and 2013) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…We did not have sufficient dietary information to evaluate overall diet quality, which is also an important lifestyle factor. Several studies have demonstrated that healthy dietary patterns were associated with lower risk of coronary heart disease and mortality in Korean adults [32][33][34] . Our findings (i.e., lifestyle risk score) do not fully capture the additional benefits of maintaining healthy diets.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have sufficient dietary information to evaluate overall diet quality, which is also an important lifestyle factor. Several studies have demonstrated that healthy dietary patterns were associated with lower risk of coronary heart disease and mortality in Korean adults [32][33][34] . Our findings (i.e., lifestyle risk score) do not fully capture the additional benefits of maintaining healthy diets.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, the DQI-K, a modified version of the DQI, was developed to reflect the specific nutrition reference intakes of Koreans. An increase in DQI-K has been correlated with an increase in mortality [ 13 ]. Therefore, it is necessary to evaluate diet quality according to specific groups or diseases in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intake data were collected during KNHANES using the 24-hour recall method and the DQI-K [ 13 ]. The DQI-K includes eight diet-related components: 1) daily protein intake, 2) percent energy from fat, 3) percent energy from saturated fat, 4) daily cholesterol intake, 5) daily whole-grain intake, 6) daily fruit intake, 7) daily vegetable intake, and 8) daily sodium intake.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, although we have adjusted for various confounding factors such as age, physical activity, chronic diseases and engagement in social activities, we cannot exclude the possibility of residual confounding from other relevant covariates which remains unaccounted for in our analyses. For example, previous studies have indicated that nutrient intake is associated with the risk of mortality45 and handgrip strength 46 47. However, we were unable to control for nutritional status due to lack of nutrition data in KLoSA.…”
Section: Discussionmentioning
confidence: 93%